2017
DOI: 10.4103/jmh.jmh_84_16
|View full text |Cite
|
Sign up to set email alerts
|

Role of vitamin D in urogenital health of geriatric participants

Abstract: Introduction:Role of Vitamin D is very well known for the functioning of many body organs. However, its role in the postmenopausal women in relation to various genitourinary disorders has been recognized recently. The main objective of this study was to evaluate role of Vitamin D in vaginal health, prolapse, bladder and bowel function, and bacterial vaginosis (BV).Materials and Methods:This was a randomized controlled study in which 200 geriatric female patients of 65–78 years of age divided into two groups co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
0
4
1
3
Order By: Relevance
“…Contrary to this hypothesis regarding that serum levels of vitamin D should be lower in patients in the case group, namely, those with PFD as compared to the control group (without PFD), the results showed that the mean serum level of the control group and the frequency of vitamin D deficient patients were higher in the control group. These results do not match the results of previous studies on the association of PFD and serum level of vitamin D (26)(27)(28), and also the correlation between the serum levels of vitamin D and urogenital disorders such as UI (20,37) and overactive bladder (21), which have determined lower serum levels of vitamin D in patients with PFD or UI problems. In this study, it was assumed that the patients were of the same social class as they referred to one center and that their dietary nutrition was also similar.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to this hypothesis regarding that serum levels of vitamin D should be lower in patients in the case group, namely, those with PFD as compared to the control group (without PFD), the results showed that the mean serum level of the control group and the frequency of vitamin D deficient patients were higher in the control group. These results do not match the results of previous studies on the association of PFD and serum level of vitamin D (26)(27)(28), and also the correlation between the serum levels of vitamin D and urogenital disorders such as UI (20,37) and overactive bladder (21), which have determined lower serum levels of vitamin D in patients with PFD or UI problems. In this study, it was assumed that the patients were of the same social class as they referred to one center and that their dietary nutrition was also similar.…”
Section: Discussioncontrasting
confidence: 99%
“…Also 47% of all the refugees in the world and 50% of asylum seekers and displaced people are women and girls and 44% refugees and asylum seekers are children under the age of 68 muscular dysfunction in pathophysiology of the UI, some studies have investigated the association of vitamin D and urogenital disorders such as UI (20) and overactive bladder (21) while others have focused on the effect of vitamin D supplementation on treatment of UI symptoms (22,23). However, based on the review studies (24), the few investigations exploring this association (25)(26)(27)(28) have several limitations and further studies are required to determine the definite correlation between vitamin D and PFD. Moreover, the prevalence of vitamin D hypovitaminosis and PFD are high among Iranian women and the relationship between these 2 variables has not been investigated in the Iranian population.…”
Section: Mortalities and Morbiditiesmentioning
confidence: 99%
“…The study also highlighted a dose-response relationship between the level of 25(OH)D and the occurrence of BV [120]. However, Kaur et al found no association between serum vitamin D levels and BV [121]. Ginkel et al concluded that women on estrogen replacement therapy are less likely to have vaginal colonization with anaerobic bacteria and that estrogen may potentiate the effects of lactobacilli on vaginal pH [122].…”
Section: The Effects Of Vitamin D On Vaginal Infectionsmentioning
confidence: 97%
“…Более того, уровень витамина D был обратно пропорционален тяжести пролапса тазовых органов [ 105 ][ 106 ]. Повышение уровня витамина D было связано с уменьшением риска расстройств тазового дна, улучшением среднего модифицированного индекса здоровья влагалища у женщин в возрастной группе 65–78 лет [ 107 ].…”
Section: дефицит витамина D и менопаузаunclassified
“…Витамин D может быть полезен при вагинальном дискомфорте у женщин в период менопаузы [ 107 ][ 115 ], однако некоторые экспериментальные результаты противоречивы [ 118 ][ 119 ]. В исследовании 2017 г. было показано, что витамин D обладает фунгицидной активностью в отношении Candida Albicans.…”
Section: дефицит витамина D и менопаузаunclassified